Socio-Demographic Factors Influencing Antenatal Care Practices in Urban Slums of Amritsar City, Punjab, India - Gill, Kanwal Preet; Devgun, Priyanka (National Journal of Community Medicine, 2013)
Objective: The study was conducted to explore socio - demographic factors influencing antenatal care in various slum areas of Amritsar city in Punjab. Methods: A total of 30 clusters of 7 units each were taken to make a sample of 210 units. The women who had delivered within one year before the interview were taken as study units. They were interviewed with the help of a pretested proforma and regression analysis was applied to evaluate the effect of various socio-demographic factors on antenatal care. Results: On univariate analysis nativity, possession of identity proof, socio-economic status of women, type of family, age of women, literacy status of women and their husbands, parity and pre-planning of pregnancy emerged as significant factors influencing antenatal care practices of the women. But, multivariate regression analysis identified only literacy of the women (OR=3.02, CI=1.36 - 7.57, p=<0.01), literacy of their husbands (OR=2.52, CI=1.13 - 5.6, p=<0.05) and socio-economic status of the household (OR= 2.25, CI=1.5 - 5.5, p=<0.05) as significant factors affecting the antenatal care practices. Conclusion: Literacy of women and their husbands and socioeconomic status of households are significant factors determining antenatal care. Therefore, efforts should be made to improve upon these factors.